Pemberdayaan Ibu dalam Stimulasi Motorik Kasar Bayi melalui Tummy Time dan Baby Yoga di PMB Lina Contesa - Suci Sulistyorini; Susmita Susmita (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Gross motor development in infancy is a crucial aspect of child growth that requires early and continuous stimulation. Limited maternal knowledge and skills in providing appropriate stimulation may hinder the achievement of infants’ gross motor milestones. This program aimed to empower mothers to stimulate infants’ gross motor development through tummy time and baby yoga at PMB Lina Contesa. A community empowerment approach with a one-group pretest–posttest design was applied. The participants were mothers with infants aged 3–12 months. The intervention included health education, demonstrations, hands-on practice, and mentoring in performing tummy time and baby yoga. Evaluation was conducted by assessing maternal knowledge and skills before and after the program. The results showed an increase in the mean knowledge score from 56.4 ± 8.7 to 85.2 ± 6.9 after the intervention. In addition, the proportion of mothers who were able to correctly perform gross motor stimulation techniques increased from 27.8% to 88.9%. These findings indicate that empowering mothers through education and training in tummy time and baby yoga is effective in improving maternal knowledge and skills and has the potential to support the optimization of infants’ gross motor development.